The Difference of Brainstem Auditory Evoked Potential Latency in Diabetic Patient with Good and Poor Glycemic Control - Samatra, D. P. G. Purwa; Meliana, Grace; Putra, I. G. N. Purna; Widyadharma, I Putu Eka (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Diabetes mellitus (DM) is a metabolic disorder which may complicate other organs, including the nervous system. Literatures which discuss about DM complications in the peripheral nervous system are easy to find but not so many of the central nervous system. Central diabetic neuropathy is a new concept which could be detected by a simple and non-invasive method, called brainstem auditory evoked potential (BAEP). AIM: The aim of the study was to find differences in BAEP latencies of a diabetic patient with good and poor glycemic control. METHODS: This was a cross-sectional study of 80 patients who came for follow-up in diabetic center and neurology polyclinic at Sanglah Hospital, from April to July 2016. The subjects were divided into two groups, depending on their glycemic control, then having BAEP examination. RESULTS: The unpaired t-test found prolonged BAEP latencies (either peak latency of wave III, V, IPL I-III, III-V, and I-V) in both ears at the poor glycemic control group, but the results were not differed significantly (p > 0.05). CONCLUSION: BAEP wave latencies were found prolonged in DM patient with poor glycemic control but not statistically significant. Further evaluation of BAEP latencies in DM patients is needed with prolonged duration and their relation with other comorbid factors, especially smoking habit.